Influence of transformational leadership, job satisfaction, and organisational commitment on organizational citizenship behavior (OCB) in XYZ hospital nurses in Lampung - Lestari, Cici Viorina; Jayanegara, Oscar (Institute of Computer Science (IOCS), 2023)
This research aimed to examine and analyze the Impact of Job Satisfaction and Transformational Leadership on Organizational Citizenship Behavior (OCB) with Organizational Commitment as a mediating variable. The study employed a quantitative research approach and hypothesis testing. Data was collected using purposive sampling with a Likert scale (1-5) questionnaire from 178 nurses working at RS XYZ in Lampung. The data was analyzed using the Partial Least Squares Structural Equation Model (PLS-SEM). The results indicate that Transformational Leadership and Job Satisfaction have a positive and significant influence on Organizational Commitment. Organizational Commitment, Transformational Leadership, and Job Satisfaction all have a positive and significant impact on Organizational Citizenship Behavior. Transformational Leadership has a positive and significant influence on OCB through Organizational Commitment, and Job Satisfaction also has a positive and significant effect on OCB through Organizational Commitment. These findings suggest that management should promote transformational leadership, enhance job satisfaction, and strengthen organizational commitment to support more positive Organizational Citizenship Behavior. This can create a motivating, productive work environment with voluntary contributions from employees, ultimately leading to improved organizational performance and success.